The effect of using two methods of feedback on the achievement of students of the College of Basic Education in the subject of geography (Journal of the College of Basic Education, 2022)
It is no longer a secret to anyone that education in its broad concept and its broad contents has an impact and importance on the lives of individuals and societies and their renewal.Rather, it is a formative group of human processes and activities connected to the stages and closely related to the individual’s internal components and the factors of his external environment, both natural and social (Shafaq 1989: 18-19), which led to the establishment of developed and developing countries alike examining their educational systems in a coordinated search for imbalances and shortcomings, as it became It is clear to these countries that their traditional educational institutions